Auditory stream segregation using amplitude modulated bandpass noise - Nie, Yingjiu; Nelson, Peggy B. (Frontiers in Psychology, 2015)
The purpose of this study was to investigate the roles of spectral overlap and amplitude modulation (AM) rate for stream segregation for noise signals, as well as to test the build-up effect based on these two cues. Segregation ability was evaluated using an objective paradigm with listeners’ attention focused on stream segregation. Stimulus sequences consisted of two interleaved sets of bandpass noise bursts (A and B bursts). The A and B bursts differed in spectrum, AM-rate, or both. The amount of the difference between the two sets of noise bursts was varied. Long and short sequences were studied to investigate the build-up effect for segregation based on spectral and AM-rate differences. Results showed the following: 1. Stream segregation ability increased with greater spectral separation. 2. Larger AM-rate separations were associated with stronger segregation abilities. 3. Spectral separation was found to elicit the build-up effect for the range of spectral differences assessed in the current study. 4. AM-rate separation interacted with spectral separation suggesting an additive effect of spectral separation and AM-rate separation on segregation build-up. The findings suggest that, when normal-hearing listeners direct their attention toward segregation, they are able to segregate auditory streams based on reduced spectral contrast cues that vary by the amount of spectral overlap. Further, regardless of the spectral separation they were able to use AM-rate difference as a secondary/weaker cue. Based on the spectral differences, listeners can segregate auditory streams better as the listening duration is prolonged—i.e. sparse spectral cues elicit build-up segregation; however, AM-rate differences only appear to elicit build-up when in combination with spectral difference cues.